Laporan Kasus : Penanganan Pada Klien Lanjut Usia Dengan Gangguan Pola Tidur Menggunakan Terapi Benson - Elok Alfiah Mawardi; Atika Jatimi; Dessy Rindiyanti Harista; Intan Sarida (Indonesian Health Science Journal, 2023)
Introduction; Sleep pattern disturbances are often experienced by individuals who experience a decline in health conditions both physically and psychologically. Sleep pattern disorders in the elderly can refer to health conditions that require further treatment through pharmacological and non-pharmacological management such as Benson therapy. Objective; to describe the effectiveness of providing Benson therapy to elderly people who experience sleep pattern disorders. Method; The implementation of this case study uses a nursing process approach through five stages, namely assessment, establishing a nursing diagnosis, developing interventions, implementing nursing plans and evaluating the results of actions. Results; After applying Benson therapy seven times, elderly people who had disturbed sleep patterns experienced an improvement in their condition. Conclusion; The evaluation results after implementing action on elderly people with sleep pattern disorders showed that the nursing problem was resolved.